2021
DOI: 10.1039/d0ta12612h
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional organic ammonium salt-modified SnO2nanoparticles toward efficient and stable planar perovskite solar cells

Abstract: Bulk and interfacial nonradiative recombination hinders the further enhancement of power conversion efficiency (PCE) and stability of SnO2-based planar perovskite solar cells (PSCs). To date, it is still a huge...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
142
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 173 publications
(155 citation statements)
references
References 46 publications
7
142
0
Order By: Relevance
“…Subsequently, the space charge limited current (SCLC) measurement was conducted to calculate the defect densities of the perovskite films, as illustrated in Figure 4J–L. The defect density was calculated by the equation n t = (2 εε 0 V TFL )/( eL 2 ), 41,42,47,48 where ε 0 is the vacuum dielectric constant, ε is the dielectric constant of the perovskite, V TFL is the trap‐filled limit voltage obtained through fitting dark I‐V curves, e is the elementary charge, and L is the thickness of perovskite film. The trap‐filled limit voltages ( V TFL ) obtained by fitting dark I‐V curves were 0.48 V for the control perovskite film, 0.35 V for the ClTPPPF 6 modified perovskite film, and 0.33 V for BrTPPPF 6 modified perovskite film.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, the space charge limited current (SCLC) measurement was conducted to calculate the defect densities of the perovskite films, as illustrated in Figure 4J–L. The defect density was calculated by the equation n t = (2 εε 0 V TFL )/( eL 2 ), 41,42,47,48 where ε 0 is the vacuum dielectric constant, ε is the dielectric constant of the perovskite, V TFL is the trap‐filled limit voltage obtained through fitting dark I‐V curves, e is the elementary charge, and L is the thickness of perovskite film. The trap‐filled limit voltages ( V TFL ) obtained by fitting dark I‐V curves were 0.48 V for the control perovskite film, 0.35 V for the ClTPPPF 6 modified perovskite film, and 0.33 V for BrTPPPF 6 modified perovskite film.…”
Section: Resultsmentioning
confidence: 99%
“…TRPL spectra were fitted according to the method reported in our previous works. 41,42,47 PL intensities were much increased after BrTPPPF 6 and ClTPPPF 6 treatment (Figure 4B). Meanwhile, the average carrier lifetimes were increased from the 549.72 ns of the pristine perovskite films to 1487.45 ns of the ClTPPPF 6 modified perovskite film and 1541.95 ns of the BrTPPPF 6 modified perovskite film (Figure 4c and Table S1).…”
Section: Effect Of Modifiers On the Quality Of Perovskite Filmsmentioning
confidence: 97%
“…The aforementioned results showed that the moisture stability was markedly increased after the incorporation of 4F-PHCl, which could be put down to the following several reasons: First, improved crystallinity and enlarged grain size could partially contribute to the improved moisture stability because reduced GB density resulted in the reduced attack active sites of water and oxygen. [19,25] Second, reduced defect density and defect-assisted nonradiative recombination due to effective defect passivation should be partially responsible for the enhanced moisture stability. [8,47] Finally, the incorporation of the hydrophobic fluorine-substituted benzene ring in 4F-PHCl should be one of the main reasons for improved moisture stability.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, organic or inorganic salt molecules have been demonstrated to be very promising considering the simultaneous passivation of anionic and cationic defects. [23][24][25] In the perovskite films, oxidized iodine (I 2 ) defects also would be generated except for point defects. Nevertheless, the work on the suppression or removal of the formation of iodine defects is reported rarely.…”
Section: Introductionmentioning
confidence: 99%
“…introduced NH 4 Cl into the SnO 2 precursor and showed that ammonium ion and chloride anion at the SnO 2 /perovskite interface can suppress the formation of deep‐level defects. [ 17 ] Additionally, some other organics (e.g., 4‐imidazoleacetic acid hydrochloride, [ 18 ] NH 4 F, [ 12b ] girard's reagent t (GRT), [ 19 ] organic ammonium salt benzyltriethylammonium chloride ([BZTAm]Cl), [ 20 ] etc. ), especially fullerene derivatives (e.g., chlorinated fullerene dimers, [ 21 ] [6,6]‐phenyl‐C61‐butyric acid methyl ester, [ 22 ] etc.…”
Section: Introductionmentioning
confidence: 99%